Investigation of a Glow Discharge with a Coaxial Hollow Cathode - Stanislav V. Pogorelov; Ihor V. Krasovskyi; Volodymyr A. Timaniuk; Nikolay G. Kokodii (East European Journal of Physics, 2022)
The article is devoted to the study of the operating modes of a glow discharge with a coaxial hollow cathode in helium and neon gases. It is shown that the burning voltage of a discharge with a coaxial hollow cathode is lower than one with a cylindrical hollow cathode of equal diameter, and the position of the optimal pressure range depends on the width of the annular gap of the cavity. It is noted that the rod current density is 3-5 times higher than the cylinder current density. The insignificant role of the photoelectric effect in the processes of electron emission from the cathode is proved. It is shown that the intensity of the atomic spectral lines of the cathode material increases significantly when a coaxial hollow cathode is used.